VALUE CREATION IN RAW GOODS SECTOR: A STUDY ON THE IMPACT OF GCG, FINANCIAL PERFORMANCE, CAPITAL STRUCTURE, AND FIRM SIZE - Yusrizal, Yusrizal; Wati, Yenny; Amalia, Annisa Nur; Tanjung, Amries Rusli; Haryadi, Teddy (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to determine the analysis of the effect of good corporate governance (GCG), profitability (ROA), leverage (DAR), capital structure (DER), and firm size (total assets) on the value of raw goods sector companies listed on the IDX 2018-2022. This study uses secondary data where the data obtained comes from the company's financial statements. The data collection technique in this study was the purposive sampling technique. The number of samples in this study was 68 companies. The method of completing this research uses quantitative analysis techniques using SmartPLS software. From this study, it is concluded that the Debt-to-Equity Ratio (DER) variable has a positive effect on company value (PBV). Meanwhile, the Audit Committee, Independent Board of Commissioners, Return on Asset (ROA), Debt to Asset Ratio (DAR), and Total Asset do not affect company value (PBV). Penelitian ini bertujuan untuk mengetahui analisis pengaruh good corporate governance (GCG), profitabilitas (ROA), leverage (DAR), struktur modal (DER), dan ukuran perusahaan (total asset) terhadap nilai perusahaan sektor barang baku yang terdaftar di BEI 2018-2022. Penelitian ini menggunakan data sekunder di mana data diperoleh berasal dari laporan keuangan perusahaan. Teknik pengumpulan data dalam penelitian ini adalah teknik purposive sampling. Jumlah sampel dalam penelitian ini adalah 68 perusahaan. Metode penyelesaian penelitian ini menggunakan teknik analisis kuantitatif dengan menggunakan software SmartPLS. Dari penelitian ini disimpulkan bahwa variabel Debt to Equity Rasio (DER) berpengaruh positif terhadap nilai perusahaan (PBV). Sedangkan untuk Komite Audit, Dewan Komisaris Independen, Return on Asset (ROA), Debt to Asset Ratio (DAR), dan Total Assets tidak berpengaruh terhadap nilai perusahaan (PBV).